2012
DOI: 10.1371/journal.pone.0045441
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between IRF6 and TGFA Genes Contribute to the Risk of Nonsyndromic Cleft Lip/Palate

Abstract: Previous evidence from tooth agenesis studies suggested IRF6 and TGFA interact. Since tooth agenesis is commonly found in individuals with cleft lip/palate (CL/P), we used four large cohorts to evaluate if IRF6 and TGFA interaction contributes to CL/P. Markers within and flanking IRF6 and TGFA genes were tested using Taqman or SYBR green chemistries for case-control analyses in 1,000 Brazilian individuals. We looked for evidence of gene-gene interaction between IRF6 and TGFA by testing if markers associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 58 publications
4
49
1
5
Order By: Relevance
“…A genome-wide linkage study of families with clefting suggested genetic differences between those with and without dental anomalies (Vieira et al 2008b). Also, previous associations between cleft candidate genes/loci, including MSX1, PAX9, IRF6, ANKS6, ERBB2, ABAC4-ARHGAP29, 8q24, and 6q14, and specific patterns of dental anomalies in individuals with clefts (Vieira et al 2004;Modesto et al 2006;Vieira et al 2008a;Letra et al 2012;Yildirim et al 2012) support the hypothesis of a common genetic link between oral clefts and dental anomalies. However, they may also be partly explained by mechanical effects of the cleft and surgery if these variants affect cleft type and severity.…”
mentioning
confidence: 65%
“…A genome-wide linkage study of families with clefting suggested genetic differences between those with and without dental anomalies (Vieira et al 2008b). Also, previous associations between cleft candidate genes/loci, including MSX1, PAX9, IRF6, ANKS6, ERBB2, ABAC4-ARHGAP29, 8q24, and 6q14, and specific patterns of dental anomalies in individuals with clefts (Vieira et al 2004;Modesto et al 2006;Vieira et al 2008a;Letra et al 2012;Yildirim et al 2012) support the hypothesis of a common genetic link between oral clefts and dental anomalies. However, they may also be partly explained by mechanical effects of the cleft and surgery if these variants affect cleft type and severity.…”
mentioning
confidence: 65%
“…The CCR3 pathway is important in neovascularization and inflammation, with the CCR3 receptor (also known as eotaxin receptor) being expressed on eosinophils, airway epithelial cells, basophils, mast cells and T2 helper cells [71]. The CCR3 receptors can be found in the human choroidal neovascular membrane and various cancers [72–74]. In a mouse model, when CCR3 is blocked then choroidal neovascular is decreased [75].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-alpha has been found in retina, neural tissues and tumors [71–73]. Abnormal interactions between TGF-alpha and the transcription factor IRF6 (interferon regulatory factor-6) are associated with tooth agenesis and cleft lip-palate development [74]. Vieira has suggested that TGF-alpha is a genetic modifier associated with developmental diseases [75].…”
Section: Discussionmentioning
confidence: 99%
“…Although heterozygous Irf6 mutant mice have normal palate formation, a combination of loss of Smad4 and inhibition of p38 MAPK only led to ~50% reduction of Irf6 expression and persistence of the MEE in ex vivo organ culture. This result suggests that there are other factors or signaling pathways that might regulate Irf6 expression in addition to SMAD4/p38 MAPK signaling pathways 1227 RESEARCH ARTICLE TGFβ-mediated Irf6 activity during palatogenesis (Ferretti et al, 2011;Letra et al, 2012). A recent study has shown that integration of IRF6 and the Notch ligand jagged 2 signaling is essential for controlling palatal adhesion and fusion during palatogenesis (Richardson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%